Modelling of A User-Driven Prosthetic Robotic Arm for Patients with Forearm Amputation - Hanifah, Hazim; Amirul Syafiq Sadun (Progress in Engineering Application and Technology, 2021)
With the growth of advanced technology and manufacturing, the design of prosthetic forearm has evolved. For example, in the past decades, numerous research has been conducted to improve the comfortability and effectiveness of prosthetic limbs such as by applying electromyographic (EMG) technique where the signal from muscle movement was processed to control the prosthetic forearm movements instead of using earlier design with fixed movement. This research was conducted to draw a design of a 3D model of the user-driven prosthetic forearm that able to perform open-palm and closed-knuckle action utilizing EMG technique. The sketching and drawing design were conducted via CAD/CAM design software to realise a 3D model design based on design data and idea obtained in a previous study. The concept idea for this design was biologically-inspired by the construction of human forearm. This paper presents the design outcome that able to satisfy the objectives stated. However, compared to the previous study, the design is still lacking to mimic an actual human forearm and can still be improved to rival the design from the previous study.